FENOMENA PINJOL SEBAGAI TAMBAHAN MODAL USAHA DI LINGKUNGAN UMKM SOLO - Stephanie Priscilla Darmawan; Yuwono Prianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The journey of human life in fulfilling the necessities of life to maintain life and achieve prosperity at an established level. In implementation, it is often accompanied by events that erode the original purpose and often turn into something that is detrimental to human life, at least to certain individuals or social groups. The development of information technology in the financial sector, disrupts the stability of life, destabilizes the joints of life together, or threatens the survival of a person, a family and colleagues, if not understood carefully. Borrowing is a shortcut to meet the needs of life or as additional capital to maintain the continuity of its business activities which are squeezed by the restrictions imposed in connection with the Covid-19 pandemic. The purpose of the study was to determine the factors that Solo UMKN chose to borrow as additional capital and to protect SMEs that were caught in the loan. The results of the study are the high level of loan complaints, illegal borrowing using debt collectors. The empirical sociological legal research method is based on primary data collection in the form of interviews, preceded by a literature study as a guide for conducting field research. Informants were determined purposively by contacting lenders, cultural figures, community leaders, religious leaders, youth leaders, government officials, legal practitioners, and academics in Solo. Use the question list as a guide. The data is processed and analyzed qualitatively using deductive logic by placing laws and regulations as the major premise and legal facts obtained through interviews as the minor premise. Digitalization intelligence places Solo micro, small and medium entrepreneurs to get additional capital from Pinjol amid the business slump experienced due to the prolonged corona pandemic. And the cunning of borrowing strategies and the cruelty of debt collectors can be avoided